Two monoclonal antibodies against glycoprotein Gn protect mice from Rift Valley Fever challenge by cooperative effects. - Benjamin Gutjahr; Markus Keller; Melanie Rissmann; Felicitas von Arnim; Susanne Jäckel; Sven Reiche; Reiner Ulrich; Martin H Groschup; Martin Eiden (PLoS Neglected Tropical Diseases, 2020)
Rift Valley fever virus (RVFV) is a zoonotic arbovirus that causes severe disease in humans and ruminants. The infection is characterized by abortions in pregnant animals, high mortality in neonates as well as febrile illness in humans that develop in 1% of cases encephalitis or hemorrhagic fever. There is presently no specific antiviral treatment for RVFV infection available. In this study, two monoclonal antibodies (mAbs), raised against glycoprotein Gn, were applied in a therapeutic study. Treatment of RVFV infected mice with neutralizing mAb Gn3 alone at two different time points (30 minutes before or 30 minutes after virus challenge) showed only moderate efficacy of about 58.3% survival in both applications. However, a combination therapy together with non-neutralizing mAb Gn32 demonstrated complete protection (100% survival) when applied 30 minutes after the lethal challenge dose. The increase of mAb efficacy is probably based on cooperative neutralization effects. These data suggest that a combination therapy with mAbs Gn3 and Gn32 could be an effective treatment option against RVFV infection.